PENGARUH HADIS TENTANG KEJUJURAN DALAM MENINGKATKAN KARAKTER MORAL PESERTA DIDIK - Rusyaid Rusyaid; Nur Aufa Wafiqotus Sholihah; Nusryabila Tamrin (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2024)
Honesty is one of the basic forms in forming a person's character, whether from the family, school or community environment. However, as time goes by, the value of honesty begins to erode. Corruption, cheating, plagiarism are forms of erosion of the value of honesty. This article will discuss the value of honesty by referring to the Bukhari Hadith. This writing uses the ma'anil hadith method and understanding the meaning. The result of this writing is that Bukhari's hadith about honesty is a valid hadith, both in terms of sanad, rawi and matan. Understanding ma'na using a linguistic approach has also explained the essence of ma'na contained in the hadith. The results of the implementation of this hadith show that the value of honesty in character education is formed from habits. Therefore, always speaking and being honest will lead to social harmony and order. Meanwhile, the habit of lying will lead to social conflict, both in real life and in cyberspace.